The Bitcoin Project and the Free Market - Mihaela Iavorschi (CES Working Papers, 2013)
The human innovation in the field of monetary freedom takes shape in the virtual communities. Developed and implemented through a decentralized algorithm, the bitcoin project has so far proved itself a success in the field of virtual currency. Beyond the technical part of operation, in this paper we will analyse the theoretical principles underlying the bitcoin. This study shows that the bitcoin largely meets the role of natural money of gold and silver, in compliance to the free market's behaviour. This allows us to observe the fact that people are aware of the negative implications the state's intervention has in the monetary filed, thus deciding to create and use their own currency in online transactions.
Keywords: F31; 330; bitcoin; crypto-currency; free market Romania